Considerations in the establishment of weight classes for wrestling - Curby, D. G. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
The decision by the international governing body for wrestling, United World Wrestling (UWW) to reorganize its weight classes, along with an increase to 10 classes for competition in non-Olympic years, provides the sport with a wonderful opportunity to create an approach that is rational, based on scientific knowledge and creates more opportunities for participation. We now have a blank slate, and while no set of weight classes can be perfect, one should be able to explain the basis for its formulation. This paper will review the history of weight classes in the sport, and attempt to put forth a rationale means for the establishment of a weight class model in the future, and also to provide an example of such a process.